The combustion of waste, industrial glycerol in a fluidised bed. (15th August 2022) - McCann, T.; Marek, E.J.; Zheng, Yaoyao; Davidson, J.F.; Hayhurst, A.N.
Graphical abstract: Highlights: Continuous burning of the waste glycerol was sustained for ∼ 4 h in a bed of silica sand. When burning waste glycerol in a bed of fluidised alumina, the bed sintered after ∼ 0.5 h. The bed particles were possibly cemented by potassium compounds, K2 SO4 and KOH. The waste pyrolysed in rising bubbles and the products burned mainly in the freeboard. Abstract: Large quantities of glycerol are produced as a somewhat useless, industrial by-product, when producing biodiesel. Thus, the combustion of this waste (containing glycerol, less volatile, non-glyceride oils, ash and water) in a fluidised bed has been investigated. The fuel entered the bottom of the bed (on its axis) as bubbles of vapour, which rose up the bed, surrounded by bubbles of fluidising air. While more difficult to burn than medicinal glycerol, continuous burning of the waste was sustained for a total of ∼ 4 h in a bed of silica sand (500 – 710 μm) at 750°C, fluidised by air. However, after ∼ 4 h, fluidisation ceased, because the silica sand agglomerated into globules a few mm wide, probably cemented by a eutectic of K2 SO4 and KOH; this industrial glycerol did originally contain potassium and sulphate ions, from its manufacture. Under similar conditions, when burning the waste in a bed of fluidised alumina (Al2 O3 ) particles (355 – 425 μm), the bed de-fluidised after almost ½ h, and then sintered into a cake, again possibly cemented by the potassium salts K2 SO4 and KOH. As for combustion, there was evidence that waste glycerol can be burned in a fluidised bed of SiO2 particles autonomously, without supplying heat. In such a fluidised bed, it appeared that glycerol vapour, inside a bubble, first decomposes thermally, yielding CO and H2 . The less volatile oils were slower to evaporate and decompose. Combustion of the waste fuel with air occurred in a bed of SiO2 particles only to a limited extent in rising bubbles, depending on the bed's depth. Otherwise, burning occurred above the fluidised particles, just as a mixture of methane or propane in air burns, when fluidising a hot bed of silica particles. The role of the particles is to inhibit combustion by scavenging radicals.